Synthesis of highly concentrated suspensions of silver nanoparticles by two versions of the chemical reduction method - Gakiya-Teruya M. (2019)
In spite of the widespread use of the chemical reduction method to obtain silver nanoparticles, the nanoparticle yield is often low due to a required addition of small volumes of diluted metal ions to a solution containing a reducer. Higher yields can be obtained following an alternative method, in which the reducer is added to a greater volume of silver ions in the solution. In this study, protocols for both methods are detailed and compared, using characterization tools such as UV-vis spectrometry, dynamic light scattering (DLS), and zeta potential measurements. By using this alternative method, the amount of silver in the solution is three times greater, and nanoparticles with a narrower size distribution are formed (between 6 and 70 nm in size). In contrast, the regular method produces particles of 3 and 100 nm. Zeta potential measurements indicate that the nanoparticles synthesized with the alternative method will be more stable than those from the regular method. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.